Fixed bed dryer: an adaptation to improve drying of natural coffee in Brazil (Research, Society and Development, 2020)
The drying of coffee by means of fixed layer dryers has been widely used by Brazilian coffee growers. However, high gradients of water content formed in these dryers are frequently reported, as well as the presence of microorganisms. The present work was developed with the purpose of monitoring the performance of these dryers and their effect on the final quality of the product, comparing to an adaptation made in conventional fixed layer dryers. During drying, the following characteristics were monitored at various points in the drying chamber: temperature of drying air, intergranular air, exhaust air, and ambient air; relative humidity of the drying air, the ambient air, and the exhaust air and the water content of the product at different points and heights in the drying chamber (0.12; 0.36 and 0.60 m). Among the dry product evaluations, color analysis and microbiological analysis were performed. According to the results obtained, drying with inversion of the airflow resulted in a water content gradient of 0.4% (b.u.), while conventional drying caused a gradient of 8% (b.u.). Regarding the color of the product in the different drying managements, drying with airflow inversion resulted in lighter products. For the microbiological analysis, fungi of the genera Cladosporium, Fusarium, and Aspergillus were found, among others. The average incidence of these fungi was higher in conventional drying samples than in fixed layer drying with inversion of airflow.